دور الحوكمة المؤسّسيّة في تطوير الأداء الأكاديمي والبحثي في مؤسّسات التّعليم العالي - لطيفة خبار; وهيبة عبيد; سعدية بلعيد; نجاح بكوشة (university of eloued جامعة الوادي, 2024)
" هدف هذا البحث إلى معرفة دور الحوكمة المؤسسية في تطوير الأداء الأكاديمي والبحثي لمؤسسات التعليم العالي، ومن أجل ذلك تم الاستعانة بالمنهج الوصفي والتحليلي في الجانب النظري، بهدف تقديم الإطار المفاهيمي لأسلوب الحوكمة المؤسسية، وكذلك الأداء الأكاديمي والبحثي في مؤسسات التعليم العالي، كما تم استخدام منهج دراسة الحالة في الجانب الميداني، للتأكد أو التحقق من طبيعة العلاقة والأثر بين تطبيق مبادئ الحوكمة المؤسسية وتطوير الأداء الأكاديمي والبحثي بالمؤسسة محل الدراسة . وبغية تحقيق هذا الهدف، فقد تم تصميم وإعداد استمارة استبيان (أسئلة) مخصصة لجمع البيانات من عينة مختارة بطريقة عشوائية بسيطة مأخوذة من 8 كليات بجامعة الشهيد حمَّة لخضر- الوادي، قُدر حجمها بــ 115 أستاذًا دائمًا، كما تم استعمال مجموعة من الأساليب والاختبارات الإحصائية ،بهدف معالج وتحليل البيانات التي تحصلنا عليها باستخدام برنامج الحزمة الإحصائية للعلوم الاجتماعية SPSS النسخة 29. ولقد توصلت الدراسة إلى عدة نتائج، ومن أهمها نذكر التالي:  أن المؤسسة محل الدراسة تقوم بتطبيق مبادئ الحوكمة المؤسسية بدرجة قوية من وجهة نظر هيئتها التدريسية.  أن المؤسسة محل الدراسة تقوم بتطبيق الأداء الأكاديمي والبحثي بدرجة قوية من وجهة نظر هيئتها التدريسية.  توجد علاقة ارتباطية طردية قوية ذات دلالة إحصائية عند مستوى المعنوية (a=0.01)، بين مبادئ الحوكمة المؤسسية الأربعة (الشفافية، الاستقلال الذاتي، المساءلة، والمشاركة) والأداء الأكاديمي والبحثي للمؤسسة محل الدراسة ،من وجهة نظر هيئتها التدريسية.  يوجد أثر ذو دلالة إحصائية عند مستوى معنوية (a=0.01) لمبادئ الحوكمة المؤسسية الأربعة (الشفافية، الاستقلال الذاتي، المساءلة، والمشاركة) على الأداء الأكاديمي والبحثي للمؤسسة محل الدراسة من وجهة نظر هيئتها التدريسية." " This study aims to explore the role of institutional governance in enhancing the academic and research performance of higher education institutions. To achieve this objective, a descriptive and analytical methodology was employed in the theoretical framework, providing a conceptual understanding of institutional governance and its impact on academic and research performance in higher education institutions. Furthermore, a case study approach was utilized in the empirical section to verify the relationship and impact of implementing institutional governance principles on the academic and research performance within the selected institution. For this purpose, a questionnaire was meticulously designed to gather data from a randomly selected sample of 115 permanent faculty members across eight colleges at the University of Martyr Hama Lakhdar - El Oued. Various statistical methods and tests were employed to process and analyze the collected data using SPSS (version 29. The study yielded several significant findings: - The institution under study strongly adheres to the principles of institutional governance, as perceived by its faculty members. - The institution also demonstrates strong adherence to academic and research performance standards, according to the faculty's perspective. - There exists a strong, positive, and statistically significant correlation (at the α = 0.01 significance level) between the four principles of institutional governance (transparency, autonomy, accountability, and participation) and the academic and research performance of the institution, as viewed by its faculty. - The four principles of institutional governance (transparency, autonomy, accountability, and participation) have a statistically significant impact (at the α = 0.01 significance level) on the academic and research performance of the institution, from the faculty's perspective."
Keywords: الحوكمة المؤسسية، الأداء الأكاديمي والبحثي، مؤسسات التعليم العالي، تطوير، جامعة الشهيد حمه لخضر بالوادي. institutional governance; academic and research performance; higher education institutions; development; University of El Oued